transparency in the national army (2016)
In tis work I do an analysis and reglexion of meaning of transparency, its dimensions the right that has acces to the information the right to have access to information, the source of law in Colombia, in the same way as the Army apply it and ensures full compliance with the law, creating within the institution a political and management transparency work in the continuous monitoring of all processes and procedures, seeking that all staff are aware of fencing through campaigns the issue, avoid questions, make recommendations to the different procedures and make support and monitoring strategic level, among other issues, with so that the final results and institutional products generated in a flexible and keeping the principles of transparency.